Estimating Belowground Carbon Stocks in Isolated Wetlands of the Northern Everglades Watershed, Central Florida, Using Ground Penetrating Radar and Aerial Imagery. Issue 11 (6th November 2017) - McClellan, Matthew; Comas, Xavier; Benscoter, Brian; Hinkle, Ross; Sumner, David
Abstract: Peat soils store a large fraction of the global soil carbon (C) pool and comprise 95% of wetland C stocks. While isolated freshwater wetlands in temperate and tropical biomes account for more than 20% of the global peatland C stock, most studies of wetland soil C have occurred in expansive peatlands in northern boreal and subarctic biomes. Furthermore, the contribution of small depressional wetlands in comparison to larger wetland systems in these environments is very uncertain. Given the fact that these wetlands are numerous and variable in terms of their internal geometry, innovative methods are needed for properly estimating belowground C stocks and their overall C contribution to the landscape. In this study, we use a combination of ground penetrating radar (GPR), aerial imagery, and direct measurements (coring) in conjunction with C core analysis to develop a relation between C stock and surface area, and estimate the contribution of subtropical depressional wetlands to the total C stock of pine flatwoods at the Disney Wilderness Preserve (DWP), Florida. Additionally, GPR surveys were able to image collapse structures underneath the peat basin of depressional wetlands, depicting lithological controls on the formation of depressional wetlands at the DWP. Results indicate the importance of depressional wetlands as critical contributors to the landscape C budget at the DWP and the potential of GPR‐based approaches for (1) rapidly and noninvasively estimating the contribution of depressional wetlands to regional C stocks and (2) evaluating the formational processes of depressional wetlands. Key Points: Isolated wetlands play a critical role in the carbon cycle and have the potential to sequester substantial amounts of carbon GPR is a valuable and minimally invasive tool to rapidly and accurately estimate carbon stocks of subtropical isolated depressional wetlands A GPR and aerial imagery relation shows the potential for regional inventory estimates of wetland carbon stocks with minimal cost and labor